(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to explain the nature of the credit guarantee companies, their objectives and the reasons for their establishment, as well as to find out the opinions of the researched sample regarding the contribution of the credit guarantee institution in protecting the rights of lenders, as it is because of the weakness of the guarantees provided by the borrowers, which is one of the most important legal requirements available to the bank, which In which the borrower undertakes to pay the value of the loan with interest, it is no longer sufficient for lenders for the possibility of non-payment risks, which necessitates an increase in guarantees to allow the protection of the rights of lenders, and to achieve the goal of the research, the researcher chose a deliberate sample consisting of (90). A person researched in the research sample consisting of six banks, which are each of the banks (Sumer, Al-Ahly Bank, Baghdad, Mosul, Elaf Al-Islami, Al-Khaleeji), using the descriptive and statistical method and the statistical program (SSPS, v25) to test the research hypothesis, and the results of the research showed that The existence of a credit guarantee institution contributes significantly to the protection of the rights of lenders (banks) to a high degree from the point of view of the researched sample.